KSU aerobic swine waste handling system - a progress report - B A Koch; G L Allee; R I Lipper; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1977)
At the KSU swine research unit, the aerobic oxidation waste-disposal system continues to function satisfactorily. Though problems and maintenance are minimal, routine observation and maintenance are necessary to prevent development of problems. Odor is not a problem. Waste fluid can be spread on fields any time that soil is not too wet and--regardless of wind direction or humidity conditions--nearby neighbors do not complain. Pigs are performing satisfactorily in all buildings. Flies are easily controlled, suitable sanitation is easily maintained, and working conditions are satisfactory.; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; KSU aerobic swine waste handling system; Aerobic oxidation